Mountain protective forests under threat? an in-depth review of global change impacts on their protective effect against natural hazards - Moos, Christine; Stritih, Ana; Teich, Michaela; Bottero, Alessandra (Frontiers in Forests and Global Change, 2023)
Forests in mountain areas provide an indispensable ecosystem service by protecting people and infrastructure against natural hazards. As forests are increasingly affected by global change, including climate change, more frequent and severe natural disturbances, and shifts in land use, open questions remain regarding the long-term and sustainable provision of this crucial protective service. To improve our understanding of the various effects of global change on protective forests, we summarized the current knowledge based on a systematic review. Focusing on changes in mountain forests’ protective effect against snow avalanches, landslides, rockfall, torrential floods and debris flow, we assessed 72 peer-reviewed, English publications. Overall, climate-induced changes are expected to increase forests’ protective effect at higher elevations but reduce it at lower elevations mainly due to increased drought. Natural disturbances usually decrease the protective effect of forests, but their impact is often further exacerbated by salvage logging. Different forest management strategies are often studied using forest simulation models, and their impacts on protective forests strongly depend on the local context and interactions with climate change. While clearcuts consistently reduce the protective effect, other forest management interventions such as thinning can have either positive or negative effects. Most of the reviewed studies were case studies based on forest simulation or process-based hazard models (but rarely combining the two) , while empirical evidence was scarce. Forests’ protective effect is often assessed using (diverse) indicators of forest structure, but evaluations of resulting risks are less common. More consistent modeling approaches linking forest structure to hazard and risk, as well as consistent indicators across different case studies, are needed for a better understanding of changes in protective forests and the service they provide under global change.